Three Area Power System Load Frequency Control Using Fuzzy Logic Controller - C. R. Balamurugan (International Journal of Applied Power Engineering (IJAPE), 2018)
System frequency is one of the most important parameters of a power system. Du to generation-load mismatches, the system frequency can vary over a small range. When the power consumed by loads and overall losses is greater than the generated power, the operating frequency of the system will decrease, resulting in a situation known as the under frequency condition. In some other case, if some of the loads in a system are disconnected from the system suddenly, or lost, it leads to a condition called as the over frequency condition. This condition is char acterized by greater input power than the consumed power by the loads. The rest of the loads in the system will absorb the extra power and the generator inertia, leading to an increase in the system frequency. In both the cases, the system frequency fluctuates from the power system’s limited frequency range, further leading to tripping off of the substation and further collapsing of the entire system. The paper describes a new method employing a smart meter to monitor and control the power system frequency which changes according to the loading conditions in the system, whether under load condition or overload condition.